PELAKSANAAN TEKNOLOGI MORTAR BUSA PADA PROYEK FLY OVER SEKIP UJUNG - Kalsum, Fhelvia Umi; Wahab, Wahyuni (Ensiklopedia of Journal, 2024)
The increasing development of construction technology in Indonesia has resulted in a variety of new innovations in its application. In concrete, for example, there have been many modifications and substitutions in the constituent materials. In the case study, cohesion soil can be applied as a mixed material with mortar-foam. This material is a local material which, when mixed with foam, will expand to four times the initial volume so that the material required is not much and the procurement of embankment material does not need to be imported from other locations. Another advantage of this method is that the weight and strength values can be planned according to needs. Foam mortar is a cement-based mixture with water, foam and fine aggregate. This mixture is called mortar because there is no coarse aggregate used in it. Foam is produced by mixing water with a foam agent derived from vegetable protein using a foam generator.Keywords: foam mortar technology